2010
DOI: 10.1345/aph.1p373
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Home Medicines Review by Pharmacists in Older Australian Patients Using the Medication Appropriateness Index

Abstract: The study demonstrates that the provision of medication reviews by accredited pharmacists can improve the appropriateness of prescribing as demonstrated by the change in MAI score and, hence, has the potential to improve patient outcomes. Pharmacists who perform medication reviews could also consider including the systematic approach of applying the MAI to assist in optimizing prescribing in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
79
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 37 publications
7
79
1
1
Order By: Relevance
“…However, community pharmacy-based studies investigating medication management of home-dwelling elderly are rare. The already published pharmacy studies report on home-based medication reviews aimed at improving the appropriateness of prescribing (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, community pharmacy-based studies investigating medication management of home-dwelling elderly are rare. The already published pharmacy studies report on home-based medication reviews aimed at improving the appropriateness of prescribing (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It has taken a generational shift over a period of nearly 20 years to begin the processes whereby these services have become inculcated in pharmacy practice outside of hospitals. It has been necessary to re-engineer the profession, creating models of advanced practice to allow skilled practitioners to deliver the services and educating pharmacists to develop the skill sets required to do so.…”
Section: The True Impact Of Changes To Professional Services Program mentioning
confidence: 99%
“…MedsChecks, Diabetes MedsChecks and Clinical Interventions by pharmacists), none of which is supported by any evidence in the context of the Australian healthcare setting. Conversely, there is evidence on the value of HMRs to consumers, 2,5,6 a demonstration of cost savings of up to $550 per HMR to the health system, 7-10 and a demonstrable track record that clearly illustrates the delivery of a truly collaborative service between GPs, patients, independent accredited pharmacists and other community or hospitalbased pharmacists [11][12][13][14][15][16][17][18] (Fig. 1).…”
mentioning
confidence: 99%
“…Australian studies have demonstrated that HMRs can resolve, manage or reduce medicine-related problems for a wide range of patients. [11][12][13][14][15][16][17][18][19][20][21] In addition, HMRs improve health outcomes; for example, in patients receiving betablockers for heart failure, an HMR resulted in a 45% reduction in likelihood of hospitalisation for heart failure at any time. 18 Another study found that an HMR in patients taking warfarin resulted in a 79% reduced likelihood of bleeding-associated hospitalisation 2-6 months after the HMR.…”
mentioning
confidence: 99%
See 1 more Smart Citation